Methods and applications of acoustics emission. Comparative analysis - MALECKI, I.; RANACHOWSKI, J. (Archives of Acoustics, 1993)
Acoustic signals which accompany internal changes of the structure of a continuous medium have been observed for centuries, and where often utilized as warning signals of oncoming catastrophes. These signals provoked also an interest as indicators of homogeneity and strength of material. [...]